The Effects of Poverty on Health Outcomes in Nigeria: An ARDL Approach - Abdulrahman Abdulganiyu Idris (Economics and Business)
There is no doubt that individual makes up a nation. Thus, as health is a crucial component of one’s welfare, access to good healthcare is a prerequisite to attaining long-term economic growth that is both sustainable and prosperous. This study looks at the impact of poverty on people’s health in Nigeria. A time series data spanning 29 years, from 1991 to 2021 was used for the study. This data was estimated using Auto Regressive Distributed Lag (ARDL). In order to simulate how poverty affects health outcomes in Nigeria, the study utilized mathematical models to determine whether Nigeria health results (CO2 emission, patients per physician, life expectancy rate, and poverty rate) responds to poverty shock. The study implies that, poverty shock has a big short-term influence on health outcome factors. The study suggested that in order to reduce high mortality rates government should focus more on improvement in health sector, particularly in the areas where there are less hospitals and basic healthcare facilities care is inadequate.